STUDI KUALITATIF PENGAMBILAN KEPUTUSAN DALAM KELUARGA TERKAIT DENGAN KOMPLIKASI PERINATAL DI KABUPATEN CIANJUR JAWA BARAT - Melani, Asti (Fakultas Kedokteran Universitas Brawijaya, 2008)
ABSTRACT The high number of maternal mortality rate caused by 3 complex problems. One of those problems was delay identification by the family on the risk factors of the maternal and make decision in seeking help related to their problem. The goal of this study was to identify how the family involvement role, especially their husband, to the maternal health and how the decision making pattern in the family, related to the perinatal complication. This study is qualitative research using phenomenology approach. The number of participant in this study were six couples husband and wife in Bojongherang, Cianjur, West Java. The findings identified that most of the decision maker in the family were the husbands, except those wife who are the carrier woman. In general, the process of decision making start with discussion from both husband and wife before the decision making is made. Some other is decided by their husband instead. The most influenced factors to the decision making process were socio-economic, accessibility to the health insurance and the family knowledge on the perinatal complications. The other less influenced factors were gender, educational background and cultural background. Key words : Decision making in the family,perinatal complication, maternal health.